What causes a small increase in radiographic progression in rheumatoid arthritis patients tapering TNF inhibitors?. Issue 1 (20th March 2017) - Bouman, Chantal A M; den Broeder, Alfons A; van der Maas, Aatke; van den Hoogen, Frank H J; Landewé, Robert B M; van Herwaarden, Noortje
Abstract : Objective: In a randomised controlled trial investigating tapering of TNF inhibitors (TNFi) compared with usual care (UC) in rheumatoid arthritis patients, minimal radiographic progression was more frequent in patients who attempted tapering. Possible explanations include higher incidence of flaring, higher mean disease activity or lower TNFi use. Methods: 18 months data from the DRESS study were used. Change in Sharp-van der Heijde (ΔSvdH) score (linear regression) and proportion of patients with >0.5 ΔSvdH (logistic regression) were used as outcomes. The cumulative incidence and number of short-lived and major flares per patient, mean time-weighted disease activity (MTW-DAS28-CRP) and TNFi use were used as independent variables. Regression models were performed stratified per study group and corrected for possible confounders. Results: 175 of 180 patients had 18-month data available. The mean ΔSvdH were 0.75 and 0.15 units with 37 of 116 (32%) and 9 of 59 (15%) patients exceeding 0.5 points in the tapering and UC group, respectively (both p<0.05). MTW-DAS28-CRP, but not incidence or number of short-lived or major flares, or TNFi use, was independently associated with the mean progression score, but only in the tapering group. Additional analyses on DAS28-CRP subcomponents showed that this was mainly caused by MTW swollen joint count. No confounders were identified. Conclusions: Radiographic progression was associated with higher MTW-DAS28-CRP (and especially swollen joint count), but only in patients who tapered TNFi. This finding stresses the importance of maintaining disease activity as low as possible in patients in whom TNFi is tapered and to check for radiographic progression regularly. Trial registration number: NTR 3216 ; Post-results.